Tipologi Pengelolaan Pendidikan Pesantren: Studi Pondok Pesantren Modern Sahid Bogor - Zaenal Arifin (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
Pondok Pesantren is an Islamic educational institution that emphasizes the value of morality in religion as a standard for conduct in daily life. Its mission is to study, learn, investigate, live, and practice Islamic teachings. Islamic boarding schools have since seen fast development and change, giving rise to a variety of shapes and styles. The dynamics of science in the pesantren environment have been impacted by changes or modernization of Islamic education in Indonesia related to the idea of Islamic modernization in this region, such as the emergence of several Islamic boarding schools, including salaf (traditional) Islamic boarding schools, kholaf (modern), and semi-kholaf (semi-modern) Islamic boarding schools. The modernisation of boarding schools for Muslims It is difficult to ignore education, as evidenced by the changes in the growth of world culture and civilization today. Without modernization, Pesantren institutions and systems struggle to advance. The modernization of pesantren institutions and systems, however, has not been without issues or criticism. Whether there is criticism or not, in some instances, the modernization of Islamic boarding schools has proven to have many positive effects that can ultimately develop the potential of Islamic boarding schools and the potential for community development in addition to being a part of national education that should be proud of in creating and educating the nation.In this instance, the Modern Sahid Bogor Islamic Boarding School is one of many Islamic boarding schools that respond to the current reform and modernization of Islamic boarding school education management. By managing education in a contemporary manner with adequate facilities and infrastructure, and based on professional management principles based on POAC; planning (planning) Organizing (o In addition to using current management techniques, Tri Darma Service Sahid current Islamic Boarding School also implements the values of noble culture, Rumongso melu handarbeni (feeling of belonging), Wajib melu hanggondeli (Must share responsibility ), Mulat saliro hangroso wani (After introspection dare to express opinions wisely), Amanah Panca Sesotya Jati, Principal of Commitment to Work, as well as Principal of Cooperation and Community. Keywords: boarding school, modern, typology, management.